Cyclic microwave-assisted synthesis of CuFeS2 nanoparticles using biomolecules as sources of sulfur and complexing agent - Aup-Ngoen K. (2014)
Copper iron sulfide (CuFeS2) nanoparticles were successfully synthesized by a 300 W cyclic microwave radiation, exposing onto ethylene glycol containing Cu(CH3COO)2, FeCl3 · 6H 2O or FeCl2 · 4H2O and L-cysteine biomolecules. X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), Raman spectrometry and X-ray photoelectron spectroscopy (XPS) revealed the presence of pure tetragonal chalcopyrite CuFeS2 nanoparticles with valence states of Cu+, Fe3+ and S2- and four Raman shifts at 215.0-218.6, 280.2-281.4, 394.4-394.9 and 472.2-473.4 cm-1. A formation mechanism of the products was also proposed according to the experimental results. © 2013 Elsevier B.V. All rights reserved.